Out-Group Mating Threat and Disease Threat Increase Implicit Negative Attitudes Toward the Out-Group Among Men - Klavina, Liga; Buunk, Abraham P.; Pollet, Thomas V. (Frontiers in Psychology, 2011)
We investigated if perceiving an out-group as a threat to one’s mating opportunities enhanced the implicit negative attitudes towards that out-group. In addition, we examined the moderating effect of disease threat on the relationship between an out-group mating threat and implicit negative attitudes toward an out-group. In Experiment 1, an out-group mating threat led to stronger implicit negative out-group attitudes as measured by the Implicit Association Test, but only for men with high chronic perceived vulnerability to disease. No such effects were found among women. In Experiment 2, men in the out-group mating threat condition, who were primed with disease prevalence showed significantly stronger implicit negative attitudes towards the out-group than controls. Findings are discussed with reference to the functional approach of prejudice and sex-specific motivational reactions to different out-group threats.